“The good, the bad and the ugly”. Bucharest’s urban core as a moral playground. - Habit, Daniel (Routledge, 2021)
This chapter explores ideological struggles over the so-called “Old Town” in the Romanian capital by retracing the dominating concepts, conflicts and contradictions within the discussions on the development of Bucharest’s central district. The historical-anthropological analysis leads from the 1970s and Ceaușescu ’s ideas of a socialist capital through the post-socialist transformation period of 1990s and 2000s to the gentrification processes and NGO activism in recent years. This area represents an important landmark in the historical self-legitimization of each political system, as its architectural heritage was curated in accordance with the leading vision of national identity – reconfiguring, reinterpreting and renaming buildings, squares, streets and monuments. Based on archival and ethnographical fieldwork, this chapter shows how ethical reasoning and arguing ascribes its own logic and value system to processes of urban change according to the needs of the various stakeholders concerned with the neighborhood by revealing their strategies, counterstrategies and social creativity in the process of acquiring both (historical) time and (material) space.
Keywords: Hauptstadt; Stadtzentrum; Historische Altstadt; Planungsleitbild; Kulturerbe; Altstadterhaltung; Kontroverse